2015
DOI: 10.1021/jacs.5b02946
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Reductive Tandem Reactions of Nitrostyrenes with Mo(CO)6 and a Palladium Catalyst To Produce 3H-Indoles

Abstract: The combination of Mo(CO)6 and 10 mol % of palladium acetate catalyzes the transformation of 2-nitroarenes to 3H-indoles through a tandem cyclization-[1,2] shift reaction of in situ generated nitrosoarenes. Mo(CO)6 appears to have dual roles in this transformation: generate CO and promote C-N bond formation to increase the yield of the N-heterocycle product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…There are several kinds of known organic reactions available to use in tandem cycloaddition reactions those are particularly attractive in organic synthesis [1][2][3][4][5]. Tandem reactions are referred to multistep one-pot reactions [6], these have many advantages over a series of individual reaction where it allow construction of complex structure in as few steps as possible, no need for a purification step, save on cost and amounts of reagents and reduce the amount of waste that is generated.…”
Section: Introductionmentioning
confidence: 99%
“…There are several kinds of known organic reactions available to use in tandem cycloaddition reactions those are particularly attractive in organic synthesis [1][2][3][4][5]. Tandem reactions are referred to multistep one-pot reactions [6], these have many advantages over a series of individual reaction where it allow construction of complex structure in as few steps as possible, no need for a purification step, save on cost and amounts of reagents and reduce the amount of waste that is generated.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Because of the challenges of substrate synthesis ands afety concerns with introducing the azide functional group, [6] we turned our attention toward developing metal-catalyzed processest hat employed an alternative electrophilic nitrogen-atom source.W e discovered that the combination of [Mo(CO) 6 ], phenanthroline and[Pd(OAc) 2 ]could trigger similar reactivity from a,b,b-trisubstituted nitrostyrenes to enable access to 3H-indoles (Scheme 1). [7] At the conclusion of this study,w ew erei nterestedi nd etermining if [Mo(CO) 6 ]c ould function as the reductant for the synthesiso fh eteroarenes,s uch as indoles. While these heterocycles have been synthesizedf rom nitroarenes or nitroalkenes using [Pd(OAc) 2 ]a nd CO, [8,9] we believed that using [Mo(CO) 6 ]a st he reductant would provide au seful alternative to these methodsb ecause it is an easily weighable solid, whose use would obviate the need to manipulate ag as.…”
mentioning
confidence: 97%
“…[10] To our surprise, when we exposed a-phenylnitrostyrene to [Mo(CO) 6 ], [Pd(OAc) 2 ]a nd phenanthroline only traces of the 3-phenylindole waso bserved. In light of our mechanistic studies, [7] which indicated that molybdenum played am ore complexr ole than just the source of CO,w e anticipated that these important N-heterocycles could be constructed from nitrostyrenes using the [Mo(CO) 6 ]s ource if the molybendum complex was segregated from the nitroarene.R ecently,S krydstrup and co-workers have reported the development of two-and three-chamber reaction vessels for Pd-catalyzed carbonylation reactions where CO is generated in one chamber, and the Pd-catalyzed process takes place in as eparate chamber. [11] Inspired by their work, we report herein aP d-catalyzed synthesis of indoles and benzimidazoles using [Mo(CO) 6 ]a st he carbon monoxide source using as imple two-chamber reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Recently,D river and co-workers reported an efficient synthesis of 3H-indoles by reductive cyclization of nitrostyrenes in the presence of Mo(CO) 6 and ac atalytic amount of Pd(OAc) 2 . [13] While o-nitrostyrenes have been recognized to be ideal precursors for indoles,t he potential of this transformation has not been fully exploited because of the moderate synthetic efficiency and harsh conditions often associated with the established protocols.I nconnection with our ongoing research program, we serendipitously discovered that aqueous titanous chloride was able to promote the reductive cyclization of o-nitrostyrenes to indoles in good to excellent yields. [14] Literature search after our own observation revealed as ingle isolated example from the group of Banwell.…”
mentioning
confidence: 99%